Power and Satisfaction Relationship in Multiple Distribution Channels An Empirical Research - Tan, Pang Yeow (2003)
Distribution channels can be viewed as social systems comprising a set of interdependent organisations, which perform all the activities that are utilised to move a product and its title from production to consumption. Because of this interdependency, there arises a need for some form of cooperation between channel members. Power is the means by which cooperation between individual channel members’ activities are coordinated and the means by which any conflict between firms is controlled. Given this scenario, the construct of satisfaction is of fundamental importance as a channel member’s satisfaction with its relationship with another firm is influenced by the level of control of the firm, and further maintain that greater satisfaction among channel members results in higher productivity within the channel. The research paper presented an attempt to examine the relationship between power and satisfaction empirically within a company’s multiple distribution channel system. It first measured power and satisfaction constructs separately and further examined their relationship to gain insight into channel interaction. An important finding emerged from the study is that while increased control over the channel members may result in more satisfactory performance, there are dangers in gaining too much control. Different channel members react differently when different types of power are exercised. While some powers will cause higher satisfaction, others may create a lower satisfaction. Channel members’ satisfaction could correlate positively or negatively either with the companies’ sources of power or the companies’ power on the channel members’ marketing activities. Hence, when firms attempt to exercise power should do so in a manner that positively influences channel members’ satisfaction, failing which could result in reduced internal efficiency in conducting channel operations.